2019
DOI: 10.3390/su11215978
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Workers with Disabilities in Production 4.0: Legal Foundations in Europe and Potentials Through Worker Assistance Systems

Abstract: The inclusion of employees with disabilities in production is an issue that has rarely been addressed by scientists from the manufacturing sector. In this article, we examine to what extent the trend towards Industry 4.0 offers potential for the inclusion of people with disabilities in Production 4.0. First, we examine relevant legal foundations and restrictions in Europe and in more detail in Austria, Italy, and Norway. Next, based on a literature review, we examine which technological aids in the form of wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 46 publications
0
18
0
3
Order By: Relevance
“…In the context of Tunisia, there are very few studies found using the concept of MI approach for measuring productivity changes across various sectors. Two studies were identified focusing on the evaluation of productivity changes across the Tunisian schools and educational institutions [39][40][41][42][43]. Zrelli and Belloumi [44] used MI for investigating the impact of environmental strategies on the Tunisian manufacturing industry during 1994-2008 by using data from 26 industries and found an average increase of 1.5% a year.…”
Section: Background Studymentioning
confidence: 99%
“…In the context of Tunisia, there are very few studies found using the concept of MI approach for measuring productivity changes across various sectors. Two studies were identified focusing on the evaluation of productivity changes across the Tunisian schools and educational institutions [39][40][41][42][43]. Zrelli and Belloumi [44] used MI for investigating the impact of environmental strategies on the Tunisian manufacturing industry during 1994-2008 by using data from 26 industries and found an average increase of 1.5% a year.…”
Section: Background Studymentioning
confidence: 99%
“…Mark et al ( 2019 ) states the importance of integrating people with disabilities into the labor market, especially now the fourth industrial revolution is taking place. In this context, different assistant technologies, such as sensorial aid systems, physical aid systems, and cognitive aid systems are discussed, albeit not empirically examined (Mark et al, 2019 ). Besides these rather theoretical considerations, there exists already some realized research on the integration of people with disabilities into the labor market.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, due to staff shortage, SWs cannot always meet each worker's needs as required to improve their abilities. Another crucial aspect is the change of the industrial environment caused by the so-called fourth industrial revolution “Industry 4.0.” With the help of digitalization, the trend in manufacturing will shift toward individual products and thus small batch sizes (Mark et al, 2019 ). Since this process will likely also affect SWs, demanding greater flexibility and agility from their employees will likely become unavoidable.…”
Section: Introductionmentioning
confidence: 99%
“…Although the declared long-term objective is the full inclusion of people with disabilities in regular working environments, this objective is still far from being met [5]. As Mark et al [6] pointed out, people with disabilities encounter difficulties in accessing jobs in the production sector.…”
Section: Context Of Disability and Sec In Spainmentioning
confidence: 99%
“…This literature review, although far from being exhaustive, suggests that the frameworks proposed in the literature do not cover simultaneously all the specific difficulties and aspects of the problem described in this paper and, as a matter of fact, we were unable to find works dealing with capacity and operations planning in the context of sheltered employment centers and workers with intellectual disabilities. Indeed, although the inclusion of persons with intellectual disabilities is well debated in the literature, most of the research focuses on psychologic [11,19,20] and social and economic aspects [6,12,34]. From a production planning perspective, little works dealing with planning of activities for workers with disabilities in the context of assembly lines [10,[35][36][37] appeared to be relevant for our research.…”
Section: Existing Integrated Planning Frameworkmentioning
confidence: 99%